The political/administrative aspects of regionalization and development in the Philippines issues, problems, and prospects - De Guzman, Raul P.; Ocampo, Romeo B.; Mariano, Vicente D.; Brillantes, Alex B. Jr. (1977)
Government, policies continually give emphasis to regionalization the assumption that this would be a more effective way to deliver government services through planning and implementation of development projects/programs. Since the 1956 government reorganization, a number of regionalization schemes have been proposed and adopted, each with separate sets of criteria considered in the determination of the regional groupings and the selection of regional centers. A new approach to sub-regional development is the integrated area development which can be classified into island development, river basin development, and metropolitan development approaches. The national departments can adopt either the bureau or department model for decentralizing administrative functions. According to PCR surveys, although physical decentralization has been effected, delegation of authority to the regional office on both substantive and administrative matters is insufficient. Similarly, other problems have been encountered like deficiency in the planning capability due to lack of planning units and personnel. If the regionalization process is to make substantial progress, it should approximate the stature of general-purpose regional governments.
Keywords: Administrative and political divisions; Public administration; Decentralization; Economic development; Regional development